Simplified algorithm for a constant speed missile - Abdul Halim, Abdul Jaafar (2007)
Disputes and unstable status of todays world must be tackled wisely and as those irresponsible parties may decide to use missile as their option weapon. This matter should be in top priority as the number of the terrorist attacks keep increasing from time to time and the technology knowledge of terrorist should not be look down upon. A suitable missile defense system for the Malaysian Army is very vital for the success of a mission. In this project, the development process of this system is customized to suit the Malaysian Army’s needs and its framework is suggested to be used for all the development projects that will be involving the military in Malaysia. The missile technology is still young in this region and it is a very vital technology for any countries to develop themselves for their own defense purposes. In this century, the sources of threat from other countries and terrorist groups towards our country have increased tremendously. The objective of the project is to realized the movement of a constant speed missile in a 2D simulation form. The simulation was performed using MATLAB 6.5 software with certain assumption and constraints such as the location of the enemy/target is stationary, no environmental factor such as gravitational, aerodynamics or propulsion of the missile to be considered and the missile itself has a constant speed and have a limited turning point. This thesis hopefully will initiate a basic concept in guiding a missile toward its target. The project was developed generally and it can be extends in terms of problem and application other investigation for future works.